Pemanfaatan Media Pembelajaran dalam Pembelajaran SKI - Saputri, Nadia; Hidayati, Noorazmah (Lembaga Yasin AlSys, 2024)
History of Islamic Cultural lessons are lessons that are closely related to past events, so that in the learning process many teachers only teach SKI material by simply telling their students. Of course in teaching and learning activities, a student who is only given a story by his teacher over time experiences boredom in learning, therefore a teacher is required to be more creative, innovative and progressive in providing learning to students so as to create a learning that is fun and even impressive . Therefore, a teacher should or should be in a digital era like this, it's time to use the media in the learning process in class. learning media is very helpful for a teacher to deliver his material so that it is easier and more enjoyable for students to accept. As for the media that can be used in SKI learning, at least two of the learning media can be used, namely Visual media which is divided into visuals that are silent or not projected and motion or projected visual media. Whereas the second use of instructional media in learning SKI is audio visual media which can be in the form of historical films or documentaries on the History of Islamic Culture.